Using strategic pauses during shared reading with preschoolers: Time for prediction is better than time for reflection when learning new words. Issue 5 (October 2019) - Read, Kirsten; Furay, Erin; Zylstra, Dana
Preschoolers can learn vocabulary through shared book reading, especially when given the opportunity to predict and/or reflect on the novel words encountered in the story. Readers often pause and encourage children to guess or repeat novel words during shared reading, and prior research has suggested a positive correlation between how much readers dramatically pause and how well words are later retained. This experimental study of 60 3- to 5-year-olds compared the effects of placing pauses before target words to encourage predictions, placing pauses after target words to encourage reflection, or not pausing at all on children's retention of novel monster names in a rhymed storybook. Children who heard dramatic pauses that invited prediction before the monsters were named identified more at test than children who heard either post-target pauses or the story read verbatim. In addition, there was an interaction between pre- vs. post-target pausing and whether the pauses were silent or replaced with an eliciting question, such that silent pauses were more effective before the target words, while eliciting questions were more effective after. Overall, dramatic silent pauses before new words in a story were found to best help children attend to and remember those new words.